Residual analysis of selected pesticides in cucumber and spinach collected from local markets of Mymensingh sadar - Islam, MA; Islam, MZ; Hossain, MK (Progressive Agriculture, 2015)
To explore the chemical contamination of vegetables available in local market of Mymensingh this research work undertaken for detection and quantification of the presence of pesticides. Standard pesticides and GC (Gas Chromatography) were used to confirm their retention times and area of eluted peaks. By comparing the retention times of standards and samples, confirmation of residual presence of pesticides were studied. A result revealed that residue of a fungicide (Common Name: Mancozeb, a.i: Symoxanil 72 wp) was found in one Cucumber sample out of three where 50 ppm quantified. On the other hand, out of 3 spinach samples, 1 of them showed presence of a insecticide (Common name: imidachloropid; a.i.: imidachloropid 20 SL) residues, which quantified as 35 ppm. Residual quantity determined in cucumber sample of BAUSesh More and spinach sample of Kewatkhali market, Mymensingh. To clarify the existing scenario in respect of all pesticide residues in vegetable sample, it would be necessary to develop all facilities for a modern analytical laboratories and skilled manpower. It may be useful for creating awareness about the available vegetables in consumers and farmers community. Progressive Agriculture 26:38-44, 2015